2013
DOI: 10.1364/josab.30.001743
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of slow self-collimated beams through a coupled zigzag-box resonator in a two-dimensional photonic crystal

Abstract: We report on the experimental realization of slow self-collimated beams by using a 10-coupled zigzag-box resonator in a two-dimensional photonic crystal. The speeds of the beams are reduced to less than 0.023c at resonant frequencies where the transmission exhibit peak values. The dispersion relation and the group velocities of the beams in the coupled resonator are well described by the tight-binding model. Time-domain simulations of selfcollimated pulses passing though the coupled resonator are also performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Since Kosaka et al demonstrated the self-collimation phenomenon of light beams in a PC [12], various self-collimation-based PC devices have been proposed and demonstrated, such as beam splitters [13][14][15][16], interferometers [17,18], polarization beam splitters [19,20], directional emitters [21,22], grating couplers [23], filters [24][25][26][27], and slow light devices [28][29][30]. Due to the unique and beneficial light-guiding properties such as diffractionless propagation along a definite direction [31,32] and easy crossing without crosstalk [33], optical devices based on the self-collimated beams have intrinsic potential for realizing high-density photonic integrated circuits.…”
Section: Introductionmentioning
confidence: 99%
“…Since Kosaka et al demonstrated the self-collimation phenomenon of light beams in a PC [12], various self-collimation-based PC devices have been proposed and demonstrated, such as beam splitters [13][14][15][16], interferometers [17,18], polarization beam splitters [19,20], directional emitters [21,22], grating couplers [23], filters [24][25][26][27], and slow light devices [28][29][30]. Due to the unique and beneficial light-guiding properties such as diffractionless propagation along a definite direction [31,32] and easy crossing without crosstalk [33], optical devices based on the self-collimated beams have intrinsic potential for realizing high-density photonic integrated circuits.…”
Section: Introductionmentioning
confidence: 99%
“…Various PC devices, such as beam splitters [13][14][15], interferometers [16][17][18], resonators [19,20], polarization beam splitters [21,22], directional emitters [23,24], and grating couplers [25] have been proposed based on the self-collimation effect. Very recently, we numerically and experimentally investigated the resonant transmission of self-collimated beams through coupled zigzag-box resonators (CZBRs) in a PC, and found that the speed of a self-collimated beam can be significantly reduced [26,27]. According to a tight-binding (TB) model, the group velocities of self-collimated beams should be less than 0.05c in the whole transmission band extending from 12.45 to 12.67 GHz.…”
Section: Introductionmentioning
confidence: 99%